RESILIENCE CHARACTERISTICS AND THEIR IMPLICATIONS FOR GUIDANCE SERVICES - Nafidina, Aqila Jasmine; Nugraha, Agung; Sulistiana , Dewang (PT Altin Riset Publishing, 2024)
This study aims to obtain an overview of the characteristics of the resilience of class XI students at SMA Negeri 2 Tasikmalaya. The background of this problem arises along with the challenges faced by students in the adaptation process at school and adjusting to the new learning system. Good resilience is needed so that students can deal with various changes and pressures in the school environment, especially in dealing with growing academic and social demands. The method used in this research is descriptive quantitative, with a research population of 432 students and a sample of 335 grade XI students at SMA Negeri 2 Tasikmalaya. Data collection was carried out using non-probability incidental sampling techniques and data analysis methods with the calculation of mean, standard deviation, percentage, and sex difference tests through SPSS 24.00. The results showed that the resilience of grade XI students at SMA Negeri 2 Tasikmalaya tended to be in the moderate category, with an average score of 51%, 49% in the optimal category, and there was no resilience in the not optimal category (0%). This study shows that resilience in grade XI students at SMA Negeri 2 Tasikmalaya is at the highest percentage in the moderate category. Based on these findings, it is recommended to develop a group guidance service program with experiential learning techniques to improve student resilience.